2017
DOI: 10.1016/j.addbeh.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Altered default mode, fronto-parietal and salience networks in adolescents with Internet addiction

Abstract: Internet addiction (IA) is a condition characterized by loss of control over Internet use, leading to a variety of negative psychosocial consequences. Recent neuroimaging studies have begun to identify IA-related changes in specific brain regions and connections. However, whether and how the interactions within and between the large-scale brain networks are disrupted in individuals with IA remain largely unexplored. Using group independent component analysis, we extracted five intrinsic connectivity networks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 41 publications
8
64
0
Order By: Relevance
“…These results indicate that the deceased coherence of brain activity in IA participants may underlie impaired executive function and weakened inhibition control of internet‐using behaviors. In some studies, both a regional increase and a decrease were found (Ding et al, ; Wang et al, ). Several factors may explain the difference in connectivity patterns related to IA.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These results indicate that the deceased coherence of brain activity in IA participants may underlie impaired executive function and weakened inhibition control of internet‐using behaviors. In some studies, both a regional increase and a decrease were found (Ding et al, ; Wang et al, ). Several factors may explain the difference in connectivity patterns related to IA.…”
Section: Discussionmentioning
confidence: 98%
“…Our result of a significant increase in the FC between the left frontal and left parietooccipital lobes in the IA group relative to HCs also supports this higher intrahemispheric connection. This frontoparietal network connection is implicated in a wide range of cognitively demanding tasks (Wang et al, ), the frontal and parietal lobes are both involved in attention networks (Corbetta & Shulman, ), and a larger and more bilateral frontoparietal network is activated in a short‐term memory task (Deprez et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those disorders include autism (16,17), attention-deficit disorder (18,19), and dementia (20,21). In addition, functional connectivity alterations have also been revealed in regard to some aspects of addictive behavior (22)(23)(24)(25). We know that inhalants affect anatomical connectivity.…”
Section: Introductionmentioning
confidence: 99%